2018
DOI: 10.1007/s11250-018-1687-3
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors associated with bovine viral diarrhea virus and bovine herpes virus-1 in Zanjan Province, Iran

Abstract: Bovine viral diarrhea virus (BVDV) and bovine herpes virus-1 (BHV-1) remain as the major pathogens with heavy economic consequences in Iran. The prevalence of antibodies against BVDV and BHV-1, the rate of BVDV persistently infected (PI) animals, and associated risk factors were evaluated in a cross-sectional study carried out in Zanjan Province, Northwest Iran, in December 2011. A total number of 562 cattle in 10 herds and five cities were randomly selected, and their serum samples were tested to detect antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A seroprevalence of 26% and 35% was previously reported in Saudi Arabia ( 27 , 28 ). Similarly, seroprevalence ranging from 25% to 80% was reported from Jordan, Sudan, Iraq, Oman, Egypt, Iran, India, and Bangladesh ( 22 , 24 26 , 29 , 36 – 38 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A seroprevalence of 26% and 35% was previously reported in Saudi Arabia ( 27 , 28 ). Similarly, seroprevalence ranging from 25% to 80% was reported from Jordan, Sudan, Iraq, Oman, Egypt, Iran, India, and Bangladesh ( 22 , 24 26 , 29 , 36 – 38 ).…”
Section: Discussionmentioning
confidence: 81%
“…The seroprevalence of BVDV in Europe was reported to vary between 60% and 85% ( 10 ). In the Middle East, seroprevalence varies from 40% in Egypt ( 24 ) to approximately 25% in Sudan ( 25 ), Iraq ( 22 ), and Iran ( 26 ). Similarly, a seroprevalence of 26% in Saudi Arabia and 35% in both Saudi Arabia and Oman was previously reported ( 27 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…In UK prevalence of BHV-1 was recorded about 83% in unvaccinated herds (Woodbine 2009). The seroprevalence of this virus has been determined from 36 to 48% in Central and South America and 14 to 60% in Africa (Straub 1990), 63 to 86% in Egypt (Mahmoud et al 2009), 36% in China (Yan et al 2008), 60.1% in India (Nandi and Kumar 2010), 10.7% in Iran (Erfani et al 2019)…”
Section: Epidemiologymentioning
confidence: 99%
“…Noaman and Nabinejad reported that the prevalence of BVDV in Isfahan Province, Iran, is 52.8 and 100% in cattle and farms, respectively [7]. In other provinces, the prevalence is almost the same [8,9].…”
Section: Introductionmentioning
confidence: 99%